Publisher Correction: Small molecule inhibition of cGAS reduces interferon expression in primary macrophages from autoimmune mice. Issue 1 (December 2017) - Vincent, Jessica; Adura, Carolina; Gao, Pu; Luz, Antonio; Lama, Lodoe; Asano, Yasutomi; Okamoto, Rei; Imaeda, Toshihiro; Aida, Jumpei; Rothamel, Katherine; Gogakos, Tasos; Steinberg, Joshua; et al.
The previously published version of this Article contained errors in Fig. 6. In panel h the units of thex axis were incorrectly given as mM and should have been given as µM. Also, the IC50 s for RU.365, RU.332 and RU.521 within panel h were incorrectly given as mM and should have been given as µM. These errors have been corrected in both the PDF and HTML versions of the Article.